Ways to improve the safety of landing aircraft in conditions of uncertainty - Казак, В.М.; Кравчук, М.П.; Будзинська, Т.В.; Міщерякова, В.Ю. (Proceedings of National Aviation University (archive), 2008)
An analysis of RNP concept at the stage of an aircraft descent and landing was made. Control algorithm of an aircraft under the conditions of uncertainty, based on the tunnel concept of landing performance using an intelligent control system, based on the neural fuzzy-logic regulator, was presented.